"Learning Our Way Through": Critical Professional Development for Social Justice in Teacher Education. Issue 1 (2nd January 2020) - Dover, Alison G.; Kressler, Benikia; Lozano, Maritza
ABSTRACT: While research indicates that critical professional development (CPD) can function as an alternative to dominant forms of top-down, anti-dialogical professional learning in K-12 settings, there is limited research on CPD in higher education, or among teacher education faculty specifically. In this article, we examine how participation in a year-long social justice-oriented faculty learning community (FLC) impacted faculty members' identities and trajectories as social justice teacher educators and scholars. Our findings indicate that CPD can meet university-based educators' hunger for community, professional learning, and strategic alliances, as well as increase their sense of efficacy and authenticity as social justice educators.